Pengaruh Kualitas Dan Bahan Baku Terhadap Tekstur Dan Rasa Donat Pada UMKM Donat Di Desa Naga Timbul - A M Hatuaon Sihite; Maringan Sianturi; Nurin Natiqoh Lubis (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of raw material quality on the texture and taste of donuts produced by the Donut MSME in Naga Timbul Village. This MSME faces challenges in producing donuts with a soft texture and delicious taste due to inconsistencies in raw materials and limited production equipment. The lack of understanding regarding the relationship between raw material quality and the final product further exacerbates this issue. This study employs a qualitative method with data collection techniques including interviews with MSME owners and employees, observations of the production process, and analysis of the raw materials used. This approach was chosen due to the MSME’s limited laboratory equipment, making the analysis more descriptive and based on firsthand experiences of business actors. The results show that the quality of raw materials significantly affects the texture and taste of donuts. High-quality raw materials, such as fresh wheat flour and other premium ingredients, produce donuts with a softer texture and better taste. Conversely, lower-quality raw materials result in harder-textured donuts with a less appealing taste. This study provides recommendations for MSMEs to pay more attention to raw material selection to improve product quality without relying on advanced equipment.